Incidence of congenital hemolytic anemias in young cholelithiasis patients - Ezer, Ali (Baishideng Publishing Group Co., Limited, 2010)
AIM: To clarify the incidence of congenital hemolytic anemias (CHA) in young cholelithiasis patients and to determine a possible screening test based on the results. METHODS: Young cholelithiasis patients (< 35 years) were invited to our outpatient clinic. Participants were asked for comorbidities and family history. The number of gallstones were recorded. Blood samples were obtained to perform a complete blood count, standard Wright-Giemsa staining, reticulocyte count, hemoglobin (Hb) electrophoresis, serum lactate dehydrogenase and bilirubin levels, and lipid profile. RESULTS: Of 3226 cholecystectomy patients, 199 were under 35 years, and 190 with no diagnosis of CHA were invited to take part in the study. Fifty three patients consented to the study. The median age was 29 years (range, 17-35 years), 5 were male and 48 were female. Twelve patients (22.6%) were diagnosed as thalassemia trait and/or ıron-deficiency anemia. Hb levels were significantly lower (P = 0.046), and mean corpuscular volume (MCV) and hematocrit levels were slightly lower (P = 0.072 and 0.082, respectively) than normal. There was also a significantly lower number of gallstones with the diagnosis (P = 0.007). CONCLUSION: In endemic regions, for young cholelithiasis patients (age under 35) with 2-5 gallstones, the clinician/surgeon should pay attention to MCV and Hb levels as indicative of CHA.